A STYLISTIC ANALYSIS OF â€œTHE RIME OF THE ANCIENT MARINERâ€ - Shaukat Khan; Sumaira Jehanzeb; Irfan Ulah; Muhammad Irfan (English Review: Journal of English Education, 2016)
If a specimen of literary art is seen as a fine tapestry of words made by the skilled seamstressâ€”the poet, then the lexis and structure of a language are the raw materialsâ€”the fabric and the threadâ€”by weaving which into specific patterns the finished product is achieved. The choice of materials and their arrangement into unique patterns always bear an image of their creator, or the artist; thus, a close view of them reveals the artistâ€™s identity and brings out the meaningful message that underlies the ornate running threads. Mostly, the students of literary studies cannot appreciate the beauty of the literary classics on their own. Consequently, they simply mimic the ideas, and sometimes even the words, of famous professional critics when asked to give their own critical judgment on the aesthetic merit or the thematic quality of a literary work in the shape of a home assignment, classroom presentation or an annual assessment test. Now, the researcher has got the inspiration for carrying out this study from an idea expounded in Widdowson (1975) that this mimicry can be replaced by genuine individual opinion if the students, or even those people who have non-academic concerns with literature, are brought to a standpoint from where they can have a closer view of the raw materials, the language resources, which are involved in the making of a literary product. And, if the product in its finished form cannot elicit a desired response from them then making them sensitive to the process of its making can be quite effective in this regard. Through the present study, an attempt has been made to show an easy access to the outlandish world of verse by means of the linguistic route which is laid with the familiar flagstones of grammar and vocabulary. Meaning thereby that in this study the elusiveness of poetry will be dealt with the precision of a social scientist, the linguist. The approach which serves as the basis of this study is not an invention of the researcher; rather, it is a well-known twentieth century approach known as stylistics (Jeffries McIntyre, 2010, p. 30). Samuel Taylor Coleridgeâ€™s famous ballad, â€œThe Rime of the Ancient Marinerâ€, being a widely read poem and bearing various stylistics features, offered itself as an ideal object for this study. The poetâ€™s aesthetic message is explored by analyzing the finest details of his linguistic expression. And, careful considerations have been made throughout the study to prevent the overlooking of any instance of deviant linguistic units or recurring patterns for interpretation because such elements contribute largely to the meaning of any literary product. The study is descriptive in its nature therefore qualitative data has been integrated with and substantiated by the quantitative one.Â  Keywords: stylistics, literature, lexical, semantic and graphological deviations